2018
DOI: 10.3389/fendo.2018.00630
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Ameliorates Streptozotocin-Induced Type 1 Diabetes in Mice by Inhibiting the HMGB1 Expression

Abstract: Type 1 diabetes (T1D) is an autoimmune disease characterized by the immune cell-mediated progressive destruction of pancreatic β-cells. High-mobility group box 1 protein (HMGB1) has been recognized as a potential immune mediator to enhance the development of T1D. So we speculated that HMGB1 inhibitors could have anti-diabetic effect. Sodium butyrate is a short fatty acid derivative possessing anti-inflammatory activity by inhibiting HMGB1. In the current study, we evaluated the effects of sodium butyrate in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…In addition, IL-1β can stimulate T-type immune cells to differentiate and produce IFN-γ. In mice, SB may inhibit pro-inflammatory response by downregulating IL-1β ( 39 ). IL-1β may be decreased by SB for ischemic stroke in middle-aged female rats ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IL-1β can stimulate T-type immune cells to differentiate and produce IFN-γ. In mice, SB may inhibit pro-inflammatory response by downregulating IL-1β ( 39 ). IL-1β may be decreased by SB for ischemic stroke in middle-aged female rats ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate is a metabolite produced as a result of fermentation by the microbiota and has been reported to play a protective role against diabetes and some types of kidney diseases. 6,7,9 However, the specific function and mechanism of butyrate in the renal fibrosis of db/db mice and HG-induced SV40-MES-13 cells has not been studied. Db/db mice have a mutation deletion of the leptin receptor and are common models used for studying type II diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Intraperitoneal injection of butyrate alleviated streptozotocin (STZ)-induced mice pancreatic injury by inhibiting the pancreatic HMGB1 and NF-κB p65 protein expression. 9 Besides, intraperitoneal injection of NaBu (sodium butyrate) (500 mg/kg/day) also ameliorated transforming growth factor-β1 (TGF-β1)-induced fibrosis and inflammation in the kidneys of STZ-induced diabetic rats. 10 Dong's study also reported that a diet containing NaBu (5 g/kg/day) alleviates albuminuria and mesangial matrix expansion by activating Nrf2 in STZ-induced diabetic mice.…”
mentioning
confidence: 99%
“…Xu et al (8) found that oral NaBu administration significantly alleviates inflammation in db/db mice by correcting intestinal microecological disorder and protecting intestinal barrier integrity. Additionally, intraperitoneal injection of NaBu alleviates streptozotocin (STZ)-induced mice pancreatic injury and inflammatory responses by downregulating the NF-κB pathway (9).…”
Section: Introductionmentioning
confidence: 99%